Culturally Inclusive Online Learning for Capacity Development Projects in International Contexts - Charlotte Nirmalani Gunawardena (Commonwealth of Learning, 2020)
This paper explores cultural inclusivity in online learning design by discussing two international capacity development projects; an online tutor mentor development program in Sri Lanka and a hybrid physician assistant training program in Ghana. Inclusivity involves establishing partnerships and conducting needs assessments to maximize the capacity that already exists within a given context, and addressing cultural factors that impact online learning: developing a learning community, negotiating identity, power, and authority, generating social presence, supporting collaboration, engaging in authentic inquiry-based learning, navigating interactions in a second language, and developing co-mentoring relationships to support learning. The paper provides a framework, WisCom (Wisdom Communities) to guide the design of culturally inclusive online learning incorporating lessons learned from international projects. By emphasising divergent thinking, consensus building, and the exploration of multiple solutions to complex, real-world problems, WisCom maximizes opportunities for participants’ diverse backgrounds and experiences to be valued.